Burkitt's lymphoma in a young boy progressing to systemic lupus erythematosus during follow-up: a case report and literature review - Liu, Chenxi; Pan, Ci; Jin, Yingying; Huang, Hua; Ding, Fei; Xu, Xuemei; Bao, Shengfang; Han, Xiqiong; Jin, Yanliang (Frontiers in Pediatrics, 2024)
Patients with systemic lupus erythematosus (SLE) have an elevated risk of cancer, particularly hematologic malignancies such as lymphoma and leukemia. However, existing studies on this topic are limited in their assessment of cancer incidence after SLE diagnosis. SLE can also be diagnosed after cancer, although such cases in children have rarely been report.Here we present the case of a 2.6-year-old boy who presented to our institute with fever and abdominal pain. Physical examination revealed a periumbilical mass, which was pathologically diagnosed as Burkitt's lymphoma. Autologous stem cell transplantation was performed to consolidate the effect of chemotherapy and reduce the risk of cancer relapse. Five years later, he was diagnosed with SLE, following the presentation of a fever with rash, positive autoantibodies, decreased complement, and kidney involvement. At the final follow-up, the patient was alive with no recurrence of Burkitt's lymphoma or disease activity of SLE.Despite the low frequency of SLE in children with lymphoma, the two conditions may be induced by a common mechanism involving B cell cloning and proliferation. Therefore, hematologists and rheumatologists should be aware of the occurrence of both cancer and SLE during patient follow-up.